LITERATURE AS PART OF THE CONTROVERSY OVER THE SREM FRONT (Heritage, 2022)
The battle on the Srem front during the final phase of the Second World War was the largest in the territory of Yugoslavia in terms of the duration and scope of human engagement. The exact number of killed fighters of the Yugoslav partisan army units has not been determined to date. In socialist Yugoslavia, the Srem Front was not a desirable topic, and among the surviving participants in the battle, there were differences in the interpretation of the events that took place there. After the death of Josip Broz Tito, the question of the historical assessment of the events on the Srem front was raised in public. The launch coincided with the opening of the Serbian question in the Yugoslav federation. Two novels, The Book of Milutin and Fathers and Forefathers, drew wider public attention to the Srem Front.Thanks to that, the Srem Front will come under the scrutiny of young historians, publicists, journalists and politicians. A special specificity is the social atmosphere in which this interest appeared, completely unprepared to look at historical events realistically. What was initiated by the writers regarding the Srem Front as a place of suffering for the Serbian people quickly became a controversial historical issue. Historiography did not provide a quality monograph that would, without ideological prejudices, answer the question of whether the Srem Front operation was necessary in that final period of the war and whether the huge casualties, mostly newly mobilized and insufficiently trained youth, could be reduced. It is interesting that the cinematography did not find inspiration for a feature film or series in the events on the Srem front. The reach of writers and their works has also left this topic between truth and controversy. Thus, the Srem Front became one of those difficult and painful topics in national history that remained insufficiently studied.
Keywords: Srem Front, Danko Popović, Slobodan Selenić, historical controversy